Iran's foreign policy in the post-Soviet era resisting the new international order - Hunter, Shireen (Praeger, 2010)
Iran's Foreign Policy in the Post-Soviet Era: Resisting the New International Order provides the first truly comprehensive, in-depth survey of Iranian foreign policy, issue by issue and country by country, since the Islamic Revolution. To help readers understand both the what and the why of Iran's role in the world and formulate useful responses to that role, the author provides a detailed analysis of Iranian foreign policy in all its dimensions